A question on whether competition authorities are the appropriate place to consider public interest considerations in the assessment of mergers in competition law? - Dlukulu, Babalwa Lumka (Department of Commercial Law, 2022)
This Dissertation examines the question of whether competition authorities are the appropriate place to consider public interest considerations in the assessment of mergers in competition law. The Dissertation does this by looking at the South African merger review process in the Competition Act, 1998 in comparison to other more developed economic jurisdiction such as the United Kingdom and the United States of America in examining the tension and criticism around the incorporation and balancing of public interest considerations and core economic consideration under the same competition law merger review process and competition authority. The South African merger review provisions as well as watershed cases such as the Wal-Mart Stores Inc and Massmart Holdings Ltd case, are considered. The Dissertation establishes that the concerns are legitimate around the potential muddying of the competition analysis with public interest considerations. Some of the concerns which arise include that: a) public interest considerations can be broad thereby creating sense of uncertainty for both parties to a merger, as well as prospective investors; b) public interest traverses areas concerning other stakeholders such as government or organised groups such as labour or business, thereby creating opportunity for interference, whether political or otherwise in the work of competition authorities; c) can increase the time spent in merger review because of the challenges in the types of evidence required to prove public interest impact; d) and/ or that competition authority officials may lack capacity and expertise to consider the public interest consideration. The Dissertation concludes that notwithstanding, the South African approach in incorporating public interest into the merger review process is legitimated by the unique socio-economic history of South Africa, and that the concerns raised are sufficiently mitigated and a delicate balance struck between core economic considerations and public interest in merger review. Competition Authorities are capable of balancing core competition concerns and public interest considerations, provided that Competition Authorities are independent; steps are taken to clarify the scope of the public interest concerns; public interest considerations are looked at within a limited scope of merger specificity; and further clarity and transparency is provided through open and transparent hearings and guidelines, amongst other features.